Consideration of Cosegregation in the Pathogenicity Classification of Genomic Variants - Jarvik, Gail P. (Am J Hum Genet, 2016)
The American College of Medical Genetics and Genomics (ACMG) and Association of Molecular Pathology (AMP) recently published important new guidelines aiming to improve and standardize the pathogenicity classification of genomic variants. The Clinical Sequencing Exploratory Research (CSER) consortium evaluated the use of these guidelines across nine laboratories. One identified obstacle to consistent usage of the ACMG-AMP guidelines is the lack of a definition of cosegregation as criteria for pathogenicity classification. Cosegregation data differ from many other types of pathogenicity data in being quantitative. However, the ACMG-AMP guidelines do not define quantitative criteria for use of these data. Here, such quantitative criteria, in an easily implementable form, are proposed.